Serum Creatine, Not Neurofilament Light, Is Elevated in CHCHD10-Linked Spinal Muscular Atrophy - Järvilehto, Julius; Harjuhaahto, Sandra; Palu, Edouard; Auranen, Mari; Kvist, Jouni; Zetterberg, Henrik; Koskivuori, Johanna; Lehtonen, Marko; Saukkonen, Anna Maija; Jokela, Manu; Ylikallio, Emil; Tyynismaa, Henna (Frontiers in Neurology, 2022)
Objective To characterize serum biomarkers in mitochondrial CHCHD10-linked spinal muscular atrophy Jokela type (SMAJ) for disease monitoring and for understanding of pathogenic mechanisms. Methods We collected serum samples from a cohort of 49 SMAJ patients, all carriers of the heterozygous c.197G>T p.G66V variant in CHCHD10. As controls, we used age-and sex-matched serum samples obtained from Helsinki Biobank. Creatine kinase and creatinine were measured by standard methods. Neurofilament light (NfL) and glial fibrillary acidic protein (GFAP) were measured with Single molecule array (Simoa), and fibroblast growth factor 21 (FGF-21) and growth differentiation factor 15 (GDF-15) with enzyme-linked immunosorbent assay. For nontargeted plasma metabolite profiling, samples were analyzed with liquid chromatography–high resolution mass spectrometry. Disease severity was evaluated retrospectively by calculating a symptom-based score. Results Axon degeneration marker NfL was unexpectedly not altered in the serum of SMAJ patients, whereas astrocytic activation marker GFAP was slightly decreased. Creatine kinase was elevated in most patients, in particular males. We identified six metabolites that were significantly altered in SMAJ patients’ serum in comparison to controls: increased creatine and pyruvate, and decreased creatinine,taurine,N-acetyl-carnosine and succinate. Creatine correlated with disease severity. Altered pyruvate and succinate indicated a metabolic response to mitochondrial dysfunction, however, lactate or mitochondrial myopathy markers FGF-21 or GDF-15 were not changed. Conclusions Biomarkers of muscle mass and damage are altered in SMAJ serum, indicating a role for skeletal muscle in disease pathogenesis in addition to neurogenic damage. Despite the minimal mitochondrial pathology in skeletal muscle, signs of a metabolic shift can be detected.